CURRENT PROBLEMS OF MODERN ECOLOGY OF UZBEKISTAN AND MEASURES TO STABILIZE ENVIRONMENTAL EMISSIONS - Gulnoza Gulmuratovna Turayeva (Western European Studies, 2024)
This article discusses environmental problems in different regions of Uzbekistan and their solutions
Keywords: Ecology; Uzbekistan; population; environment